Interplay Among Classroom Environment, Grit, and Enjoyment in Shaping Feedback-Seeking Behavior in L2 Writing - Wenqian Luan; Jianqiang Quan (Behavioral Sciences)
The interplay among classroom environment, grit, and enjoyment in shaping the feedback-seeking behavior (FSB) of Chinese English as a Foreign Language (EFL) learners remains underexplored. This study investigates how the classroom psychological environment and L2 grit influence FSB, categorized as feedback monitoring (FM, the passive observation of feedback) and feedback inquiry (FI, proactive requests for clarification), in the context of L2 writing. This study also focuses on the mediating role of foreign language enjoyment (FLE) in this process. A mixed-methods design was utilized to study 612 Chinese junior secondary students aged 13–15 with over five years of formal English instruction. Structural equation modeling (SEM) revealed that perseverance of effort (POE) and consistency of interest (COI), as two dimensions of L2 grit, directly predicted FM (β = 0.19 and 0.27, respectively) but not FI. The classroom environment indirectly enhanced both FM (β = 0.05) and FI (β = 0.09) through FLE. Qualitative interviews highlighted cultural constraints: 83.3% of participants prioritized FM over FI due to face-saving norms, despite high grit levels (M = 3.61 on a 5-point scale), underscoring cultural barriers to proactive feedback-seeking in Chinese collectivist classrooms. These findings validate the tripartite framework of positive psychology in L2 learning and propose strategies to balance institutional support, grit cultivation, and cultural sensitivity in fostering adaptive FSB.